2007
DOI: 10.1590/s1415-47572007000400032
|View full text |Cite
|
Sign up to set email alerts
|

Expression of D-type cyclins in differentiating cells of the mouse spinal cord

Abstract: The D-type cyclins form complexes with the cyclin dependent (CD) kinases CDK4 and CDK6 and promote the G1-S phase transition of the cell cycle by antagonizing the retinoblastoma suppresser protein pRB. In the developing nervous system D-type cyclins show spatially and temporally dynamic patterns of expression. We demonstrated that cyclin D1 was transiently expressed in differentiating spinal cord ventral interneurons while cyclin D3 protein was expressed in differentiating motor neurons and dorsal interneurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Here, for example, Celsr1 , Frzb (also known as Sfrp3 ) and Sfrp5 (or its homologs Sfrp1/2 ) functional studies revealed that their inhibition is linked to enhanced stem cell maintenance (Boucherie [ 82 85 ]. Vice versa, we could detect upregulated proliferation-enhancing genes of the Wnt pathway like Ccnd2 known to be expressed during midbrain development [ 86 88 ]. We thus conclude that known proliferative effects on midbrain NSC through physioxia might be mediated through Wnt pathways and differ compared to cortical cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, for example, Celsr1 , Frzb (also known as Sfrp3 ) and Sfrp5 (or its homologs Sfrp1/2 ) functional studies revealed that their inhibition is linked to enhanced stem cell maintenance (Boucherie [ 82 85 ]. Vice versa, we could detect upregulated proliferation-enhancing genes of the Wnt pathway like Ccnd2 known to be expressed during midbrain development [ 86 88 ]. We thus conclude that known proliferative effects on midbrain NSC through physioxia might be mediated through Wnt pathways and differ compared to cortical cells.…”
Section: Discussionmentioning
confidence: 99%